Development of Interactive Learning Video at Grade X Senior High School - Ahmad Ramadana (Chemistry Education Department, 2022)
The lack of development of learning media in schools causes students to have difficulty understanding chemical bonding material. The use of chemistry textbooks in the study of chemical bonds is not enough to reduce the abstraction of the object of the study. The lack of use of the technology-based website in developing interactive video learning media is a major problem. Measuring the student's responses to the interactive learning video on the chemical bonding material. This study uses the ADDIE development model. This study begins by analyzing the problems and limitations encountered in chemistry learning. The quality of interactive video learning media with an assessment percentage of 92.5% by media experts, 91.66% by material experts, and 88.12% by teacher practitioners. Based on the results of testing on 31 students, the percentage of assessment was 84.66% which had a very good category. Web-Based Interactive Learning Videos on Chemical Bonding Grade X in Senior High School were declared valid based on expert and practitioner assessments. Results of the assessments of these experts consistently categorize H5P as very good or good. The general assessment of this video is very good and can be used. It consists of the background, objective, methods, results, and conclusion of the research.